يبرعلا عمتجملل ميقلا رشن يف اهرودو بدلأا بتك (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Literature books play a pivotal role in spreading values and culture in Arab societies. These books are distinguished by their ability to bridge the gaps between the past and the present, and strengthen the cultural and heritage identity of the Arab nation. Through novels, short stories, and poetry, she presents social, political, and spiritual themes in a way that enriches collective understanding . Literature books highlight important issues such as social justice, equality, and freedom, which contributes to stimulating public debate and critical thinking. It also works to promote tolerance and understanding between different cultures inside and outside the Arab society. Also, it plays a role in teaching new generations about their history and traditions, helping to preserve the Arabic language and heritage . In addition, literature books provide opportunities for self-expression and creative innovation, which enriches the literary arena and stimulates cultural innovation. In this context, literary works are vital tools for education and awareness, as well as being a source of inspiration and pleasure for readers of different ages.In general, literature books contribute to promoting positive values and provide a mirror that reflects the different challenges and aspirations of the Arab society, making them an essential element in culture and education.